If one root of the equation can be expressed as where , and are square-free numbers, then find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let a = x + x 2
Note that since x is not 0, a is defined for all roots. Also, the equation is equivalent to the following: a 2 − 4 a − 2 0 = 0 . To see this we divide the original equation by x 2 and add 4 on both sides to get \[ \begin{array}{} & x^{2}-4x-16+4-\frac {8}{x}+\frac {4}{x^{2}} \\ & =x^{2}+4+\frac {4}{x^{2}}-4 (x+\frac {2}{x})-16 \\ & =a^{2}-4a-16 \\ & =4. \end{array}\] The quadratic equation a 2 − 4 a − 2 0 = 0 follows.
Now we solve it using the quadratic formula to get a = 2 + 2 6 , 2 − 2 6 . From a = x + x 2 we get two quadratic equations in the form x 2 − a x + 2 = 0 . Solving them, we have x = 1 + 6 ± ( 2 + 3 ) , 1 − 6 ± ( 2 − 3 ) . Only 1 + 6 + 2 + 3 is in the required form. Hence the answer is 1 + 2 × 3 × 6 = 3 7